Análise das relações das tensões de entrada de inversores multiníveis híbridos conectados em cascata para minimizar a THD da tensão de saída - Hoppen, Hueslei (2012)
This Master Thesis presents a study considering multilevel inverters formed from two and three level cascaded inverters. The literature presents several papers on asymmetric multilevel inverters and most studies are related to control and/or modulation techniques considering a binary or trinary topology. Also, there are studies that consider a small variation of the inverters input voltage and analyses the system behavior. However, any of these studies performs analysis to obtain the best relation between input voltage of the multilevel system, while this together with switching angles are capable of generating an output voltage with minimum THD. This Master Thesis was developed aiming to get this voltage relation for multilevel systems formed by two and three level inverters. Furthermore, it seeks to find a pattern for the voltage ratio for several cascaded inverters. To obtain the desired results, techniques of selective harmonic elimination was applied to reduce low order harmonics, reducing the need for output filter. To reduce the computational efforts for obtaining the switching angles, the author used considerations of genetic algorithms. This is necessary due to the significant increase of the variables to be determined as the number of cascaded inverters increase.